A new species of asterinaceous fungi, Asterina imbertiae sp. nov. from Kerala, India - Sabeena, Aliyarukunju; Biju, Haridas; Dhanusha, Sudhakaran Sujatha (Phytotaxa, 2021)
A new black mildew fungus, Asterina imbertiae infecting leaves of an endemic plant Garcinia imbertii (Clusiaceae) collected from Pandipath and Ponmudi forest areas, Thiruvananthapuram, Kerala is described and illustrated based on morphology. A taxonomic description and illustrations are provided. A key and a table are also given for Asterina species occurring on Clusiaceae.